Your character has been robbed. Do you want to sue the other player? Polish criminal law and the notion of “theft” in a computer game. - Olczyk, Adam (Replay. The Polish Journal of Game Studies, 2014)
Technological development implies a lot of new ways to commit crimes in cyberspace. Stealing virtual objects (such as magical swords or shoes) is one of them. It is unique because virtual theft combines one of the oldest types of criminal activity with the achievements of modern technology. This article deals with those situations when the actions taken by players stop being protected by the ‘magic circle’ and become criminal. It will also explore how the Polish Penal Law deals with these matters. It shall also discuss a comparable U.S. based case, involving fraud committed by the player called Cally in Eve Online, three cases from Poland and finally, It will deal with stipulated solutions.